The effect of centrality to lifestyle and experience-involvement on tourist behavioral intention: A comparison of hotel vs hostel - Maia, M.; Dias, Á.; Pereira, L. (Leisure Sciences, 2026)
A tourist has an authentic and memorable experience when the experience plays a central role in lifestyle and experience involvement. As such, this study aims to investigate the role of centrality to lifestyle and experience-involvement (E-I) dimensions (emotional, mental, flow-like, and social) in revisit and word-of-mouth (WOM) intentions through the mediating roles of experience memorability and experience authenticity. Survey data from two samples (traditional hotel and hostel guests) was tested using PLS-SEM to show the importance of the E-I’s mental, flow-like, and social dimensions in the memorability and perceived authenticity of the experience. Results also reveal a positive indirect effect of mental, flow-like, and social E-I on revisit and WOM intention. Moreover, the results were analyzed and compared considering the two types of tourist accommodations, hotels and hostels. The conclusion discusses the study’s practical implications and potential future research directions.